2021
DOI: 10.3390/ijerph182312279
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Adolescents’ Cyberbullying under Floods and the COVID-19 Pandemic: Parent–Child Relationships and Negotiable Fate as Moderators

Abstract: Since the outbreak of coronavirus disease 2019 (COVID-19), adolescents in 70 countries have suffered the COVID-19 pandemic and flood disasters simultaneously. Although antecedent cyberbullying variables have attracted significant research attention, the effects of psychological distress and the potential mechanisms of cyberbullying among adolescents under multiple disasters remains unclear. Based on social-ecological system theory, this study examines the moderating effects of parent–child relationships and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 64 publications
0
20
0
2
Order By: Relevance
“…These two studies gathered data before the COVID-19 pandemic. When compared to recent studies, it was found that cyberbullying increased dramatically during the COVID-19 era [29,30]. Subsequently, with the massive mandate of world online communication in teaching and learning, young adolescents faced a large amount of cyberspace exposure with all risk-related inquiries.…”
Section: Discussionmentioning
confidence: 95%
“…These two studies gathered data before the COVID-19 pandemic. When compared to recent studies, it was found that cyberbullying increased dramatically during the COVID-19 era [29,30]. Subsequently, with the massive mandate of world online communication in teaching and learning, young adolescents faced a large amount of cyberspace exposure with all risk-related inquiries.…”
Section: Discussionmentioning
confidence: 95%
“…Estudo anterior demonstrou uma relação positiva entre a presença de comportamento de cyberbullying e estresse psicológico em desastres, podendo esse estado agressivo ser um reflexo dos altos níveis de ansiedade e estresse gerado pelo cenário de crise extrema e uma forma de mitigar esses sentimentos indesejados. Nesse sentido, a realização dessa ação agressiva através da internet pode se caracterizar como uma via de alívio da agressividade gerada pela vivência de desastres como a pandemia, principalmente quando se trata de pessoas imaturas como crianças e adolescentes (Zhang et al, 2021).…”
Section: Discussionunclassified
“…Além disso, a presença ou ausência de conflitos com a família influencia bastante a extensão do impacto psicológico que o cyberbullying pode ter em crianças e adolescentes, bem como no modo de lidar com isso. Nos casos em que havia sofrimento dessa agressão, mas as vítimas tinham uma relação estreita e harmônica com seus pais, o estresse psicológico foi menor, e a capacidade de superar e adotar estratégias ativas de enfrentamento foi maior, comparado com casos de vítimas que conviviam com muitos conflitos familiares e careciam de diálogo no lar (Zhang et al, 2021).…”
Section: Discussionunclassified
“…Participants reported their gender and parents' educational levels (i.e., socioeconomic status, where 1 = primary school or less, 2 = junior high school, 3 = senior high school, 4 = college education, and 5 = master's or doctoral education). The mean scores for parents' educational levels were calculated, with higher scores representing a higher socioeconomic status (Yang et al, 2010;Zhang et al, 2021aZhang et al, , 2021b.…”
Section: Pcsmentioning
confidence: 99%
“…According to ecological system theory, parental factors, as important micro-system factors, may interact with individual factors (e.g., career exploration) in adolescent development (Bronfenbrenner, 1977). Although numerous studies have demonstrated the role of general parenting behavior in adolescent social development outcomes (e.g., LS, empathy, and cyberbullying) (Avci & Sak, 2018; Liang et al, 2021; Nainee et al, 2021; Wu et al, 2021; Zhang et al, 2021b), few studies have explored the role of specific parenting behaviors related to career development. “Career-specific parental behaviors refer to the concrete actions parents use to guide the career development of their children” (Dietrich & Kracke, 2009; Guan et al, 2015, p. 95).…”
Section: The Moderating Role Of Parental Career Supportmentioning
confidence: 99%